A Randomized Controlled Trial of Sertraline in Young Children With Autism Spectrum Disorder - Potter, Laura A.; Scholze, Danielle A.; Biag, Hazel Maridith B.; Schneider, Andrea; Chen, Yanjun; Nguyen, Danh V.; Rajaratnam, Akash; Rivera, Susan M.; Dwyer, Patrick S.; Tassone, Flora; Al Olaby, Reem R.; Choudhary, Nimrah S.; et al. (Frontiers in Psychiatry, 2019)
Objective: Selective serotonin reuptake inhibitors like sertraline have been shown in observational studies and anecdotal reports to improve language development in young children with fragile X syndrome (FXS). A previous controlled trial of sertraline in young children with FXS found significant improvement in expressive language development as measured by the Mullen Scales of Early Learning (MSEL) among those with comorbid autism spectrum disorder (ASD) in post hoc analysis, prompting the authors to probe whether sertraline is also indicated in nonsyndromic ASD. Methods: The authors evaluated the efficacy of 6 months of treatment with low-dose sertraline in a randomized, double-blind, placebo-controlled trial in 58 children with ASD aged 24 to 72 months. Results: 179 subjects were screened for eligibility, and 58 were randomized to sertraline (32) or placebo (26). Eight subjects from the sertraline arm and five from the placebo arm discontinued. Intent-to-treat analysis showed no significant difference from placebo on the primary outcomes (MSEL expressive language raw score and age equivalent combined score) or secondary outcomes. Sertraline was well tolerated, with no difference in side effects between sertraline and placebo groups. No serious adverse events possibly related to study treatment occurred. Conclusion: This randomized controlled trial of sertraline treatment showed no benefit with respect to primary or secondary outcome measures. For the 6-month period, treatment in young children with ASD appears safe, although the long-term side effects of low-dose sertraline in early childhood are unknown. Clinicaltrials.gov Identifier: NCT02385799